From bottlenecks to inflation: Impact of global supply-chain disruptions on inflation in select Asian economies - Reizle Jade C. Platitas; Jan Christopher G. Ocampo (Latin American Journal of Central Banking (LAJCB), 2025)
Supply-chain bottlenecks emerged alongside unprecedented inflationary surges amid the resulting mismatches in supply and demand for goods and services throughout the COVID-19 pandemic. This study employs a local projection approach to investigate the inflationary impact of global supply-chain pressures in the Philippines and select East Asian neighbors. We find that supply-chain disruptions are followed by sizable and statistically significant increases in headline inflation in the Philippines, Rep. of Korea, Thailand, and Singapore. Supply-chain shocks also have a considerable impact on the tradable segment of core inflation. Meanwhile, non-tradable inflation has a generally smaller, short-lived, and insignificant response to global supply-chain pressures reflecting the limited presence of second-round, indirect effects.
Keywords: E31; E52; F10; C1; 330; Global supply chains; Inflation; Monetary policy